Sosialisasi Difusi Padi Varietas Unggul Baru (VUB) untuk Meningkatkan Kapasitas dan Mutu Produksi Petani Penangkar Benih Padi - Yudi Lani Aljawas Salampessy; Nurul Annazhifah; Zahratul Millah (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
One of the rice seed producers in Lebak Regency, Banten Province, is Poktan Motekar, which carries the mission of “Improving the quality and availability of rice seeds through independent and sustainable seed cultivation.” Poktan Motekar produces an average of 140 tons of unhusked rice (paddy)/ha/season. Approximately 134 tons are sold as milled rice at a price of IDR 7,000–8,000/kg. Meanwhile, around 5 tons are allocated for seed production and marketed through local and inter-community networks of Poktan at a price of IDR 12,000/kg, despite the fact that both demand and selling price for rice seeds are generally higher. This condition is mainly due to intense competition with seed producers from other regions. Therefore, efforts to empower farmers in Lebak Regency can be undertaken by enhancing the capacity and quality of rice seed production among members of Poktan Motekar through improved knowledge and skills in cultivating newly released superior rice varieties (Varietas Unggul Baru/ VUB). Community empowerment was carried out using the innovation diffusion method, namely through the delivery of materials and interactive discussions regarding the VUB Mantap variety as an innovation to strengthen the capacity and quality of rice production. Pre-tests and post-tests were employed to measure changes in farmers’ knowledge levels about the VUB Mantap variety. The results of data analysis indicated a significant improvement in farmers’s knowledge regarding the VUB Mantap variety after participating in the innovation diffusion activity. This enhanced knowledge was expected to foster farmers’s interest in adopting the VUB Mantap variety to improve both the capacity and quality of their rice production.